Impact of fining agents on the volatile composition of sparkling mead - Pascoal, Ananias (2019)
Sparkling mead is obtained by secondary fermentation of the mead involving the addition of starter yeast culture, sucrose, nutrients and fining agents. The aim of this study was to evaluate the effect of different fining agents (tannins vs combined fining agents) on the volatile composition of sparkling mead. Sparkling mead was produced from a base mead using a commercial yeast strain (Saccharomyces bayanus) and the volatile compounds were determined by gas chromatographyflame ionisation detection and gas chromatographymass spectrometry. Thirty six volatile compounds were quantified and the major groups were alcohols (73.2%), acetates (19.1%), carbonyl compounds (5.5%) and ethyl esters (1.2%), represented by 3methyl1butanol, ethyl acetate, acetaldehyde and monoethyl succinate, respectively. The remaining compounds were present at <1%. Eleven volatile compounds exhibited odour activity values >1, with ethyl octanoate and ethyl hexanoate contributing to the aroma of sparkling mead, with fruity, strawberry and sweet notes. The combined fining agents caused a marked decrease in the concentration of volatile compounds compared with tannins. In general, 3ethoxy1propanol, ethyl lactate, ethyl octanoate, diethyl succinate, diethyl malate, monoethyl succinate, 2methylpropanoic acid, hexanoic acid, octanoic acid, acetaldehyde, acetoin, furfural, benzaldehyde, 5hydroxymethylfurfural, transfuran linalool oxide, cisfuran linalool oxide and 4oxoisophorone decreased in concentration. Conversely, 1propanol and 2methylpropanoic acid (tannins) and ethyl butyrate (combined fining agents) increased in concentration. The remaining volatile compounds were not affected. Significant differences (p < 0.05) were found for 19 volatile compounds independently of the type of fining agents used. © 2018 The Institute of Brewing & Distilling